If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8c + -10c + -6 = 10 Reorder the terms: -6 + 8c + -10c = 10 Combine like terms: 8c + -10c = -2c -6 + -2c = 10 Solving -6 + -2c = 10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2c = 10 + 6 Combine like terms: -6 + 6 = 0 0 + -2c = 10 + 6 -2c = 10 + 6 Combine like terms: 10 + 6 = 16 -2c = 16 Divide each side by '-2'. c = -8 Simplifying c = -8
| -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 | | (23x+64y)+(33x-16y)= | | 4a-2(a+6)= | | a/3=7/10 | | (43x+60y)+(38x-23y)= | | (79x+76y)-(16x+40y)= | | -3x-13=6x+23 | | 16/b=2/3 | | y+3y+2y=12 |